Treatment OF Post dural puncture headache (PDPH) after caesarean section: a review of clinical trial articles conducted in Iran - Pourya Adibi; Navid Kalani; Majid Vatankhah; Bibi Mona Razavi; Somayeh Mehrpour; Tayyebeh Zarei; Hasan Zabetian; Elahe Rahmanian (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2022)
Introduction: Headache is one of the common problems after spinal anesthesia following cesarean surgery. Various pharmacological methods have been proposed for the treatment of headache after spinal anesthesia. This study was conducted with aim to evaluate headache after spinal anesthesia following caesarean section in the form of a narrative review of clinical trial articles conducted in Iran.Methods: In this narrative review study, to find related studies, the Persian language databases of "SID", "Magiran" and the Google Scholar and English language databases of Scopus, PubMed, and Web of Science were searched with the keywords of PDPH, spinal anesthesia and cesarean section wiyhout time limitation.Results: In this narrative review study, 29 articles were examined. The reviewed studies were done from 2007-2022. The investigated drugs include: Pregabalin, gabapentin, theophylline, ondansetron, aminophylline, dexamethasone, caffeine, mannitol, intravenous acetaminophen (paracetamol), normal saline, propofol and hydrocortisone. Among the investigated drugs, dexamethasone has been most effective in controlling PDPH, and then, ondansetron has been most effective in reducing and controlling PDPH.Conclusion: The present study showed good evidence on the effectiveness of the drugs investigated in the studies. It seems that all the investigated drugs can be used as a treatment for headache (PDPH) after spinal anesthesia in cesarean section women; however, among the investigated drugs, since more studies have been performed on dexamethasone, it can be a more suitable choice for preventing headache after spinal anesthesia in cesarean section women.